(untitled) (Homoeopathy for All, 2025)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder characterized by persistent patterns of inattention, hyperactivity, and impulsivity, which significantly impact daily functioning and developmental progress. Conventional treatments often focus on symptom management; however, homeopathy offers a holistic approach by addressing underlying predispositions and restoring balance. This article explores the epidemiology, etiology, clinical characteristics, and diagnostic criteria of ADHD while highlighting various homeopathic therapies. By providing an individualized treatment approach, homeopathy aims to enhance overall well-being and long-term symptom control. This review underscores the potential benefits of homeopathy as a complementary treatment option for ADHD.